Entrepreneurial Intention of Business Students Inside Pokhara Valley - Lamichhane, Baburam (INTELLIGENCE Journal of Multidisciplinary Research, 2023)
Entrepreneurship creates a significant opportunity for individuals to achieve financial independence and benefit the economy by contributing to job creation, innovation, and economic growth. Most universities offer courses and programs in entrepreneurship. However, there is little understanding of the factors that affect students’ intentions of becoming entrepreneurs and the role of their family business background on students’ entrepreneurial attitudes and intentions. Thus, the objective of this study is to analyze entrepreneurial intention among both undergraduates and graduate students of business in Pokhara Valley. The sample size of the study is 150 has been taken as a purposive sampling technique. Along with that, questionnaires have been distributed to the business students of Pokhara. This study applied descriptive and analytical research design, which uses a quantitative method to meet the objective. The data analysis found that respondents are highly interested in entrepreneurship as a career and they prefer to become entrepreneurs most rather than going abroad or do a job. From the analysis of the study, the dependent variable entrepreneurial Intention has a significant relationship with independent variables personal attitude and interest and relational support whereas; it doesn’t have any significant relationship with structural support, entrepreneurship education, and family occupation. Therefore, through the data analysis concerning entrepreneurship, the results have many implications. First, since business students are persuaded towards entrepreneurship as a career, they should be given tremendous opportunities and environment. Second, entrepreneurship education should be improved with additional training to fulfil the intention of entrepreneurship. Thus, this study has tried to present the real scenario of the entrepreneurial intention of business students in Pokhara.